Institutional Analysis of Fish Consumption Improvement in Silo District - Selamet, Mohammad Adi; Yuliana, Ernik; Rusdiyanto, Edi (Gema Wiralodra, 2025)
Fish consumption is essential for health as it is rich in protein, omega-3, vitamins, and minerals. Increasing fish consumption requires support from effective institutions, including government policies and distribution infrastructure. Innovations such as “Catering Sehat” (Catering Sehat) and Gemarikan (Gerakan Memasyarakatkan Makan Ikan or the Movement to Encourage Fish Consumption) aim to boost fish consumption by providing nutritious meals for families at risk of stunting. This study aims to identify the issues, the actors/institutions involved, the necessary programs and activities, and to analyze public and stakeholder perceptions of the regulations and institutions supporting fish consumption in Silo District, Jember Regency. The research was conducted from October to November 2024 using a quantitative method with questionnaires distributed to 100 pregnant women or mothers of children under two (Baduta) and five experts. Data analysis was performed using Interpretative Structural Modeling (ISM). The findings reveal that inadequate knowledge of fish’s nutritional content, influenced by low education levels, is a key factor contributing to low fish consumption. All institutions – including the Fisheries Office, BAPPEDA, Health Office (Dinkes), DKPP, DP3AKB, the District Stunting Reduction Acceleration Team (TPPS), Pemerintah Desa, Rumah Desa Sehat (RDS), Posyandu, Non-Governmental Organizations, Community Leaders, and Public/ Private Universities – play a crucial role in promoting fish consumption. Efforts such as nutritional fulfillment, Catering Sehat, and Gemarikan programs are essential initiatives to enhance fish consumption.